RESEARCH OF PSYCHOLOGICAL CHARACTERISTICS OF UNEMPLOYED PERSONS AS A BASIC CONDITION OF DEPENDENCY PREVENTION (Academia Science Repository, 2023)
The economic situation in society is characterised by a reduction in production, a change in the nature of business relations and a general decline in business activity, which entails a reduction in jobs. Unemployment has become not only a factor in our lives, but also a factor in the mindset of people, their psychological state as well as social tensions. In pursuit of this task, and in an attempt to adequately reflect the realities of life for the unemployed, we have carried out research on this topic, drawing heavily on the experience of employment service practitioners. This makes it possible already now to state the confusion, depression, crisis, fear, uselessness, and material difficulties that accompany a person who has lost his job.